Effects and mechanisms of SGLT2 inhibitors on the NLRP3 inflammasome, with a focus on atherosclerosis - Yang, Liu; Zhang, Xuejiao; Wang, Qing (Frontiers in Endocrinology, 2022)
Atherosclerosis is a lipid-driven chronic inflammatory disease that is widespread in the walls of large and medium-sized arteries. Its pathogenesis is not fully understood. The currently known pathogenesis includes activation of pro-inflammatory signaling pathways in the body, increased oxidative stress, and increased expression of cytokines/chemokines. In the innate immune response, inflammatory vesicles are an important component with the ability to promote the expression and maturation of inflammatory factors, release large amounts of inflammatory cytokines, trigger a cascade of inflammatory responses, and clear pathogens and damaged cells. Studies in the last few years have demonstrated that NLRP3 inflammatory vesicles play a crucial role in the development of atherosclerosis as well as its complications. Several studies have shown that NLRP3 binding to ligands promotes inflammasome formation, activates caspase-1, and ultimately promotes its maturation and the maturation and production of IL-1β and IL-18. IL-1β and IL-18 are considered to be the two most prominent inflammatory cytokines in the inflammasome that promote the development of atherosclerosis. SGLT2 inhibitors are novel hypoglycemic agents that also have significant antiatherosclerotic effects. However, their exact mechanism is not yet clear. This article is a review of the literature on the effects and mechanisms of SGLT2 inhibitors on the NLRP3 inflammasome, focusing on their role in antiatherosclerosis.